Impact of the absence of legal frameworks containing mechanisms for adopting technological transformations Improving the public facility in Algeria - طراد طارق; صادقي فوزية (International Journal of Social Communication, 2021)
Algeria sought to provide distinct public services to the citizen by gradually eliminating central bureaucratic management, and ensuring a quality service that meets his aspirations, beginning with the adoption of the electronic management project, so there were several bets that made the public facility a priority to overcome, especially since many countries of the world rushed to adopt projects that It raises service levels and merges into the dimensions of digital transformation, and specializes it in an integrated legal framework. However, the Algerian legislature did not devote digitalization to legal systems that enable Algeria to improve the public space, and the reason for that absence is a clear poor quality of public services in all Algerian institutions.